The Odyssey - Homer (Atria Books, 2013)
A new translation of Homer's work of "one-eyed man-eating giants; irresistibly seductive sirens; shipwrecks and narrow escapes; princesses and monsters; ghosts sipping blood at the Underworld's portal, desperate for a chance to speak to the living; and the final destruction of all of Odysseus's enemies in the banquet hall"--Dust jacket flap.